Restricted Outbreak of American Tegumentary Leishmaniasis with high microfocal transmission - Krolewiecki, Alejandro Javier (2013)
Cutaneous leishmaniasis is endemic in Salta, the northwestern province of Argentina. We describe an outbreak involving five recreational hunters whose exposure was limited to several hours in a residual patch of primary forest. All patients presented with typical cutaneous lesions after a mean incubation period of 59 days (range 15–78), and one developed simultaneous mucosal involvement. Polymerase chain reaction analysis of lesions confirmed Leishmania (V.) braziliensis as the etiologic agent in three cases. All patients were cured with anti-Leishmania treatment. Entomologic surveys in the transmission area revealed a predominance of Lutzomyia neivai. This outbreak report confirms a microfocal transmission pattern of tegumentary leishmaniasis in the Americas and based on a well-determined exposure, allows the determination of incubation times for leishmaniasis caused by Leishmania braziliensis.